2,2 `-Biimidazolium 5-amino-2,4,6-tribromoisophthalate - Zhang, Kou-Lin; Huang, Han; Ng, S.W. (International Union of Crystallography, 2010)
In the cation of the title salt, C6H8N42+center dot C8H2Br3NO42, the dihedral angle between the two five-membered rings is 2.1 (3)degrees. In the anion, the mean planes of the carboxyl units are twisted from the benzene ring by 84.3 (4) and 86.2 (3)degrees. In the crystal, the components are linked by imidazolium-carboxylate N-H center dot center dot center dot O hydrogen bonds, generating a chain running along [1 (1) over bar0].